Sistem Informasi Pengarsipan Surat di Kantor Dinas Ketenagakerjaan Kabupaten Asahan - Syahrizal Syahrizal (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This Letter Archiving Information System is designed to enhance the efficiency and effectiveness of document management at the Department of Manpower Office in Asahan Regency. The system focuses on managing incoming and outgoing letters, which are routine tasks performed by an agenda officer as part of administrative duties. The management of incoming letters includes receiving, verifying, recording, and archiving, while outgoing letter management begins with drafting and continues to the delivery process. To support these processes, the system separates the management of letters into two main parts: incoming and outgoing letters. For incoming letters, data such as letter number, date, content, attachments, and destination are recorded and stored automatically. Meanwhile, outgoing letters follow a similar format to streamline the recording process and minimize manual errors. The system is developed using web-based technology, including HTML and other supporting tools, to ensure flexibility and ease of access for users. With the implementation of this system, it is expected that letter archiving can be carried out more efficiently, effectively, and accurately, thereby improving administrative performance at the Department of Manpower Office in Asahan Regency.